Sulfur dioxide induces vascular relaxation through PI3K/Akt/eNOS and NO/cGMP signaling pathways in rats. (August 2020) - Zhang, Q; Lyu, W; Yu, M; Niu, Y
Sulfur dioxide (SO2 ) is a common exogenous atmospheric pollutant. Studies have shown that SO2 can cause vasodilation as a gas signaling molecule, but the specific signaling pathways are not well understood. This study aimed to explore the underlying mechanism behind the effects of SO2 on vasodilation of isolated rat aorta. The results showed that when the dose of SO2 was 30 μM, the vasodilation of endothelium-intact rings was partially suppressed by LY294002 and N G -nitro-l -arginine methyl ester, and the protein levels of phosphoinositide 3-kinase (PI3K), p-Akt, and p -endothelial nitric oxide synthase ( p -eNOS) were significantly increased. When the dose of SO2 was 300 μM or 1500 μM, the vasodilation of endothelium-denuded rings did not change after application of the inhibitor, but the protein levels of PI3K, p-Akt, and p-eNOS were significantly decreased, and the activity of NOS and the level of nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) were significantly increased. We speculate that the mechanism of SO2 -induced vasodilatation likely involved the endothelial PI3K/Akt/eNOS and NO/cGMP signal pathways. In addition, at the concentration of 1500 μM, SO2 markedly increased the level of caspase-3 and caspase-9. The results suggest that high concentrations of SO2 may cause damage to blood vessels. This study will help to further inform the etiologies of SO2 -related cardiovascular disease.